ANALISIS KESALAHAN BAHASA DALAM BIDANG MORFOLOGI PADA SURAT KABAR KOMPAS.COM (EDISI NOVEMBER-DESEMBER 2021) - Elan Halid (Asosiasi dosen IDEBAHASA KEPRI, 2022)
The issue to be addressed in this study is the investigation of morphological language errors in the November-December 2021 edition of Kompas.com. Language errors are common in situations or professions that need consistency in language standards, particularly language usage, which prioritizes things other than communication as the end consequence of language practices. Morphology is the development of words according to their shape and meaning in expressions. According to the Great Indonesian Dictionary, newspapers are sheets of paper on which news organized into columns is printed daily or regularly. This research information comes from the newspaper Kompas.com. The data collection methods for this study are: (a) collecting the November-December 2021 edition of the Kompas.com newspaper, and (b) reading the November-December 2021 edition of the Kompas.com newspaper. The study found 81 data from 31 news articles. The investigation of language errors in morphology covers affix selection errors, word repetition errors, compound word compile errors, and word choice errors. This study concludes that word choice errors are more frequently reported.